Analysis of the Implementation of the K13 Learning Process in Vocational High Schools - Oroh, Rolly Robert; Bahrun, Lusi Maryana; Langguna, Ayu Patricya; Matandatu, Stevani; Tulus, Pieter R.R.I. (Jurnal Ilmiah Global Education, 2024)
Vocational high school (VHS) is an educational unit that functions to prepare students to become graduates with good work competencies. Student work competency can be obtained through good learning process standards. This research aims to determine the level of implementation of the 2013 curriculum (K13) learning process at VHS. This research uses a quantitative descriptive approach. This research took place at a vocational school in Manado City, North Sulawesi, Indonesia, as a case study location. The data collection technique uses a questionnaire with indicators of the implementation of the learning process, namely preliminary, core and closing activities. The data analysis technique uses descriptive analysis. The research results showed that the preliminary learning activities were declared very good with a percentage of 94%, the core learning activities were declared very good with a percentage of 92%, and the closing activities were declared very good with a percentage of 97%.